Pastoral Disabilitas dalam Gereja Katolik: Meninjau Tantangan dan Peluang Pelayanan Inklusif - Emanuela Dona Tey Henriques; Klemensia Nini; Sebastiana Unitly (Jurnal Pelayanan Pastoral, 2025)
This article examines the pastoral approach to persons with disabilities within the Catholic Church, highlighting the various challenges and opportunities in building an inclusive and just ministry. The study is motivated by the reality that persons with disabilities often continue to experience marginalization in ecclesial life physically, socially, and spiritually. Using a qualitative research method within a theological-pastoral framework, data were gathered through the review of official Church documents, theological literature, and critical reflections on pastoral practices in Catholic communities. The findings reveal that although the Church has issued several documents emphasizing the importance of inclusivity as urged by Pope Francis in the encyclicals Fratelli Tutti and Evangelii Gaudium to make the Church a home for all actual implementation of these principles at the parish and grassroots community levels still faces numerous obstacles. These include a lack of awareness about disability issues, limited accessible facilities and infrastructure, and insufficient training for pastoral workers. This study also identifies several opportunities for development, including the renewal of pastoral education curricula to be more responsive to disability issues, strengthening community networks, and utilizing digital technology to encourage the active participation of persons with disabilities in the life of faith. The author concludes that a transformation of the pastoral paradigm toward a more transformative and participatory approach is urgently needed to realize the Church as a truly inclusive and solidaristic "home for all."